Kienböck Disease: Postoperative Radiographs at Long-Term Follow-Up - Blanco, Roque H. (J Wrist Surg, 2016)
We present the radiographic results of four patients with Kienböck disease who had undergone a simple lunate excision at 26, 30, 35, and 43 years after surgery.